Client‐Related Factors Associated with a "Less than Good" Experience of Midwifery Care during Childbirth in the Netherlands. Issue 1 (1st December 2016) - Baas, Carien I.; Wiegers, Therese A.; de Cock, T. Paul; Erwich, Jan Jaap H. M.; Spelten, Evelien R.; de Boer, Michiel R.; Hutton, Eileen K.
Abstract: Background: A "less than good" experience during childbirth can affect a mother's early interaction with her child and may significantly influence a woman's emotional well‐being. In this study, we focus on clients who experienced midwifery care provided during childbirth as "less than good" care. The aim of this study was to understand the relationship between client‐related factors and the experience of midwifery care during childbirth to improve this care. Methods: This study was part of the "DELIVER study" where mothers report on the care they received. We used generalized estimation equations to control for correlations within midwife practices. Forward multivariate logistic regression analyses were conducted to model the client‐related factors associated with the experienced midwifery care during childbirth. Results: We included the responses of 2, 377 women. In the multivariable logistic regression model, odds of reporting "less than good care" were significantly higher for women who experienced an unplanned cesarean birth (OR 2.21 [CI 1.19–4.09]), an instrumental birth (OR 1.55 [CI 1.08–2.23]), and less control during the dilation phase (OR 0.98 [CI 0.97–0.99]) and pushing phase (OR 0.98 [CI 0.97–0.99]). Discussion: Birth‐related factors were more likely than maternal characteristics to be associated with the experience of midwifery care during childbirth. We conclude that there is room for midwives to improve their care for women during childbirth particularly in improving the patient centeredness of the care provider, using strategies to enhance sense of control, and focusing on the particular needs of those who experience instrumental vaginal or unplanned cesarean births.